RETRACTED: PKCε Activation Restores Loss of PKCε, Manganese Superoxide Dismutase, Vascular Endothelial Growth Factor, and Microvessels in Aged and Alzheimer’s Disease Hippocampus - Millien, Guetchyn; Wang, Huaixing; Zhang, Zongxiu; Alkon, Dan L.; Hongpaisan, Jarin (Frontiers in Aging Neuroscience, 2022)
Vascular endothelial dysfunction and capillary loss are currently considered to be a primary phenotype of normal human aging and Alzheimer’s disease (AD). Activation of protein kinase C (PKCε) improves several molecular, cellular, physiological, and behavioral endpoints, yet it is not known whether a loss of PKCε activity occurs in the microvascular endothelium in aged and AD hippocampi, whether this loss contributes to microvascular change, or whether activation of PKCε protects against microvascular damage, an early change that induces age-associated memory defect and AD. We investigated the effect of the PKCε activation on microvascular loss in the hippocampus. important for memory storage. In cultured human brain microvascular endothelial cells, tert-butyl hydroperoxide induced oxidative stress and a decrease in MnSOD mRNA and protein expression that were blocked by the antioxidant drugs. The PKCε activators bryostatin and DCPLA methyl ester increased PKCε, associated with an increase in MnSOD mRNA and its protein as well as VEGF, which was inhibited by the mRNA-stabilizing HuR inhibitors In rats (> 24 months old) and AD transgenic mice Tg2576 (5 months old), bryostatin or DCP-LA prevented a decrease in vascular PKCε, MnSOD, and VEGF and prevented microvascular loss and age-related memory impairment. An autopsy-confirmed AD hippocampus showed a decrease in PKCε and MnSOD mRNAs and their proteins and VEGF as well as in microvascular density compared to non-AD controls. In conclusion, the PKCε activation can rescue a decrease in PKCε, MnSOD, and VEGF via posttranscription regulation and alleviate oxidative stress, and in doing so, prevent microvascular loss during aging and AD.